The Effect of Pesticide Exposure on Metabolic Syndrome: An Epidemiological Analysis in an Agricultural Population - Putri Arida Ipmawati; Rusmiati Rusmiati; Suharno Suharno; Tommy Denie Irianto; Alfino Validita Sidiq; Abentin Estim; Slamet Wardoyo (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Metabolic syndrome, characterised by hyperglycaemia, dyslipi-daemia, hypertension, and central obesity, is a global health problem, and exposure to pesticides is an important risk factor for agricultural workers. This study aims to analyse the effects of pesticide exposure, sociodemographic factors, and Personal Protective Equipment (PPE) usage behaviour on glucose levels, HDL, and LDL in farmers in Kubu Raya District, West Kalimantan. A cross-sectional study was conducted on 60 farmers selected using stratified random sampling. Data were collected through structured interviews, fasting blood tests, and analysed using the chi-square test with a significance level of 95%. The results showed a high prevalence of high blood glucose (56.7%), low HDL (35.0%), and high LDL (55.0%). Pesticide exposure was significantly associated with glucose levels (p=0.043), with hypergly-caemia being higher in the high-exposure group (70.8%) compared to the low-exposure group (33.3%). Age was also significant for glucose (p = 0.046), with a higher prevalence in the ≥40 years group (65.8%) compared to the 40 years group (40.9%). The use of PPE showed a significant association with all metabolic parameters: higher glucose levels were more common in the non-routine PPE use group (70.6% vs. 38.5%; p = 0.012), lower HDL levels were higher in the non-routine group (44.1% vs. 23.1%; p=0.043), and higher LDL levels were more common in the non-routine group (64.7% vs. 42.3%; p = 0.046). These findings confirm that pesticide exposure, age, and APD usage behaviour contribute to metabolic disorders among farmers. Occupational health interventions emphasizing APD use, routine metabolic screening, and community-based education are needed to reduce the risk of metabolic syndrome in the agricultural population.